Exploring Coping Strategies of Different Generations of Students Starting University - Takács, Rita; Takács, Szabolcs; T Kárász, Judit; Horváth, Zoltán; Oláh, Attila (Frontiers in Psychology, 2021)
Introduction: Coping strategies and adaptation skills are key features in successfully adjusting to university challenges. Coping skills are an essential part of the Psychological immune system, which leads to successful adaptation. Due to COVID-19 most universities have changed their face-to-face teaching for online education. Nevertheless, there is little concrete empirical evidence on how this generation of students with the ongoing impacts of disruptive changes can cope with it. Colleges and universities need to make changes in order to retain this new generation of students. Our aim was to explore the characteristics and changes in coping skills of university students from three different age groups. Method: Psychological coping skills were measured by the Psychological Immune Competence Inventory (PICI). Differences were detected between generations. Group comparisons (pre-2004, pre-Covid, and post-Covid) groups were compared) using PICI subscales using independent sample analysis of variance. The sample consisted of 4,731 university students, 2,768 (58.5%) were men and 1,730 (36.56%) were women. Results: Students from 2004 showed significantly higher scores in the Self-regulation subsystem scale compared to students in the pre-Covid and post-Covid groups. Self-regulation subsystem: F(2, 2,569.607) = 444.375, p < 0.001, η2 = 0.27: small effect, ω2 = 0.27; Resilience: F(2, 2,372.117) = 1171.855, p < 0.001, η2 = 0.14: small effect, ω2 = 0.14. Based on the results, the explained variance ratio was at least 10% based on self-regulation and resilience. Conclusions: Psychological immune capacity of students seems to decrease through the years. Nonetheless, interventions may have a further facilitating role in the maintenance and development of psychological immunity during college years.